KINETIC OF COPPER ADSORPTION IN CALCAREOUS SOIL - & Al-Robiaee, Al-Janabi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
Laboratory experiment was carried out to study kinetic of copper adsorption using silt clay loam calcareous Iraqi soil. 5ml of copper nitrate solutions (0,25,100 and500 mg Cu L-1)that were prepared from Cu(NO3)2.3H2O Added to (soil) and (soil+compost) treatments. Compost (0.05gm) was added to (soil+compost) treatment that equal 10g kg-1 soil. The soil samples were incubated at 293±2 K for four incubation periods 24,168,336 and 672 h using Batch equilibrium technique. At each incubation period the soluble copper was determined and kinetic equations were tested. The results showed that the soil had high fixation capacity to copper at all concentrations and treatment. The percentage of copper adsorption was 99.72% at first incubation period followed by gradual increase till the pseudo equilibrium at 336h at all concentration (25,100 and 500 mg Cu L-1 solution). Compost application increased the copper fixation capacity and the copper adsorption curves showed the continuation of adsorption from 24 h. to 336 h. incubation period followed by little release of copper at 672 h. at all concentration and treatments. The power function equation was best described the adsorption of copper and copper adsorption constant (Ka) ranged from 3x10-4 to 5.5x10-3 mg Cu kg-1 h-1, which indicate to the high adsorption capacity of such alkaline soil to adsorb Cu and this will be related to Cu fertilizer management.